Depression and HIV/AIDS: adapting and piloting group interpersonal therapy for treatment of depressive symptoms for people living with HIV/AIDS in Northwest Ethiopia - Yirdaw, Biksegn (Department of Psychiatry and Mental Health, 2021)
Background Being diagnosed with HIV/AIDS and commencement of lifelong antiretroviral therapy (ART) with the requirement of high adherence can exacerbate or trigger depressive disorders. Prevalence of major depression is substantially higher in people living with HIV/AIDS (PLWHA) than those in the general population. More than 50% of PLWHA are likely to meet one or more criteria for depression in their lifetime. However, access to interventions for depressive disorders remains limited in Low- and Middle-Income Countries (LMICs) where more than 90% of people with depressive disorders are not receiving formal treatment. The role of evidence-based psychological treatments has been fundamental in reducing the huge treatment gap in LMICs. Although brief, flexible and effective psychological treatments are emerging, issues in relation to their acceptability, feasibility and effectiveness in HIV populations remain unexplored. Therefore, this thesis aimed to adapt and pilot group interpersonal therapy (IPT) for treatment of depressive symptoms including its acceptability and feasibility for PLWHA. This thesis has been the first that attempted to adapt and pilot group IPT for treatment of depression in the HIV population in Ethiopia. The findings of this thesis can serve as a baseline for researchers interested in adapting or developing psychological treatments in the HIV population in Ethiopia. The findings contribute information on the process used in examining acceptability and feasibility of psychological interventions which provides indications for conducting future trials to test the effectiveness of group IPT. Methods First, a systematic review and meta-analysis of randomised controlled trials was conducted to identify the most effective psychological treatments for depressive symptoms for PLWHA in LMICs. Second, a survey of major depressive disorder (MDD) was conducted among PLWHA who were attending ART follow-up appointments at the Felege-Hiwot Referral Hospital (FHRH) in Northwest Ethiopia. The survey served as a baseline to identify cases for piloting of group IPT and helped to identify areas for intervention. Third, the intervention areas were further explored among stakeholders from the ART clinic including PLWHA and this was followed by a stepwise adaptation of the group IPT manual. Furthermore, a formative qualitative study was conducted to examine explanatory models of depression and to explore acceptable contexts for implementation of group IPT. A total of three focus groups were conducted with purposively selected case managers, adherence supporters and service users 2 at the ART clinic. The qualitative data were analysed based on a framework approach using predefined thematic concepts. Fourth, a pilot study of the group IPT intervention was conducted among PLWHA to evaluate the acceptability and feasibility of peer-administered group IPT for treatment of depressive symptoms for PLWHA in Ethiopia. A single-arm, prepost, peer-administered, group IPT interventional study was conducted with 31 consecutively recruited participants. The participants were assigned to four IPT groups for the intervention. A post-intervention evaluation of depressive symptoms, perceived social support (PSS), functional disability and quality of life (QoL) was conducted using the same instruments used at the baseline. No control group was included in this pilot study. Results The findings of the systematic review and meta-analysis revealed that trials that used IPT have shown good effectiveness in treating depressive symptoms of PLWHA in LMICs. The baseline study found 32.5% prevalence of MDD among randomly selected PLWHA (N=393). MDD was positively associated with reduced adherence to ART, functional disability and negatively associated with overall QoL. Overall findings of the baseline and the qualitative study indicated that psychosocial problems are the most important factors that need intervention for depression for PLWHA. The main findings in relation to the adaptation of the WHO group IPT were: i) an IPT group that contains five to ten people was perceived to be acceptable and mixed gender groups were recommended; ii) sessions were recommended to be conducted in private rooms for 1.5 to 2 hours, and on a weekly basis. Findings of the pilot study indicated that depression scores reduced significantly between baseline and postintervention (mean difference (MD)=9.92; t=-7.82; p<0.001). The mean PSS scores (MD=0.79; t=2.84; p=0.009) and the mean QoL scores (MD=0.39, t=4.58, p<0.001) improved significantly between baseline and post-intervention. All the IPT intervention areas (life change, disagreement, grief and loneliness) were found to be applicable to and important areas associated with depression in PLWHA in Ethiopia. Most importantly, disagreement within a family and life change due to HIV/AIDS, such as sickness and separation were faced by almost all PLWHA included in the study, followed by loneliness or social isolation as result of HIV stigma, and grief due to loss of loved ones including a spouse, a child, a mother or a father. Overall evaluation of the pilot indicated that the procedures and outcomes of group based IPT were perceived as acceptable. Participants of the intervention gained benefits in resolving psychosocial problems and reported high satisfaction with counsellors and intervention setting. The eight weekly sessions that lasted around two hours were acceptable; however, 3 additional sessions were recommended by some counsellors until everyone recovers from depression. Conclusion The overall findings of this thesis suggested that group IPT was found to be acceptable and feasible for PLWHA in Ethiopia. Future studies should focus on examining its effectiveness for treating depressive disorders among PLWHA in Ethiopia.